2013
DOI: 10.5546/aap.2013.e1
|View full text |Cite
|
Sign up to set email alerts
|

Esparganosis cerebral. Presentación de un caso pediátrico

Abstract: Presentación de casos clínicos RESUMENSe presenta el caso de un niño de 8 años con antecedentes de epilepsia en quien el examen anatomopatológico del material extraído de una lesión de 2,5 por 3 cm localizada en la zona corticosubcortical del lóbulo occipital derecho reveló la presencia de un proceso inflamatorio crónico granulomatoso con una larva de Spirometras pp. El paciente nació y vivió varios años en una zona rural de Tarija (Bolivia). Es el primer ejemplo pediátrico de esta infestación parasitaria a ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The three cases were diagnosed in individuals from bordering countries. Two of the cases occurred in adults, one with brain localization (Boero et al, 1991) and the other with cutaneous localization (De Roodt et al, 1993), whereas the third case occurred in a child (Jones et al, 2013). In Argentina, no local cases of sparganosis have been detected yet.…”
Section: Resultsmentioning
confidence: 99%
“…The three cases were diagnosed in individuals from bordering countries. Two of the cases occurred in adults, one with brain localization (Boero et al, 1991) and the other with cutaneous localization (De Roodt et al, 1993), whereas the third case occurred in a child (Jones et al, 2013). In Argentina, no local cases of sparganosis have been detected yet.…”
Section: Resultsmentioning
confidence: 99%
“…Sparganosis is a rare parasitic disease caused by an infection by the second-stage larvae of Spirometra mansoni , also called “sparganum”. There is a higher prevalence of this disease in East Asian countries, such as China, Thailand, Korea and Japan, although sparganosis also occurs occasionally in Europe, North Americaand South America[18].…”
Section: Introductionmentioning
confidence: 99%
“…Two cases occurred in adults; one with brain localization (Boero et al, 1991) and the other with cutaneous localization (De Roodt et al, 1993). In addition, Jones et al (2013) have reported one case of Cerebral Sparganosis in a child. But all this cases were individuals of bordering countries.…”
Section: Discussionmentioning
confidence: 99%